The Impact of Oil Prices on The Transportation Industry Stock Returns: The Case of the Turkish Equity Market - Türker Açıkgöz; Özge Sezgin Alp (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2023)
This study examines the impact of crude oil prices on Turkey's transportation sector stock returns. For this purpose, ARDL Bound Test approach is utilized to investigate both long-run and short-run impacts. Research findings show that crude oil prices have an adverse impact on stock returns in the short-run since oil is a crucial input for transportation firms. However, in the long-run, increasing oil prices enhance stock returns in the sector. The oligopolistic market structure of the industry can explain this result. This study also investigates the impact of other factors on stock returns, such as macroeconomic activity, aggregate stock market performance, and global economic policy uncertainty. The results imply that transportation sector returns are also highly sensitive to macroeconomic and aggregate stock market performances. On the other hand, global economic policy has no significant impact on stock returns in the sector. Besides its academic contribution to the literature, the findings of this research offer precious practical implications for financial investors, industry stakeholders, and policymakers.